B. subtilis biofilm as a cybernetic system - Blaznik, Mojca; Stopar, David (Frontiers in Bacteriology, 2024)
Here, we view biofilm as a nested cybernetic system that cannot be studied in isolation from the dynamics in the rest of the ecosystem. We provide a systems view of B. subtilis development from the inoculation to hibernation. We propose that B. subtilis biofilm development in an aqueous environment is a temporal response to changes in the ecosystem provoked and caused by bacteria. We show that the initial bacterial growth changes physio-chemical parameters of the ecosystem, which in turn trigger the initiation of the biofilm formation and guide its development, structure, and ultimately its decay and dispersion. Formation of the biofilm is just one of the possible outputs of the bacterial cybernetic system. It is not invariably the best response that fits all environmental needs. Viewing biofilm as a cybernetic set of interrelated objects, capable of receiving, storing, processing, and exchanging information with the rest of the ecosystem, should become an integral part of biofilm studies.